2017
DOI: 10.1002/jcp.26016
|View full text |Cite
|
Sign up to set email alerts
|

Low shear stress induces endothelial reactive oxygen species via the AT1R/eNOS/NO pathway

Abstract: Reactive oxygen species (ROS) contribute to many aspects of physiological and pathological cardiovascular processes. However, the underlying mechanism of ROS induction by low shear stress (LSS) remains unclear. Accumulating evidence has shown that the angiotensin II type 1 receptor (AT1R) is involved in inflammation, apoptosis, and ROS production. Our aim was to explore the role of AT1R in LSS-mediated ROS induction. We exposed human umbilical vein endothelial cells (HUVECs) to LSS (3 dyn/cm ) for different pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…LSS can also cause oxidative stress and promote the occurrence of AS [25]. In the present study, we found that LSS significantly reduced the activity of SOD and GSH and significantly increased the levels of ROS, MDA, and GSSG, breaking the "oxidation-reduction" balance of EC.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…LSS can also cause oxidative stress and promote the occurrence of AS [25]. In the present study, we found that LSS significantly reduced the activity of SOD and GSH and significantly increased the levels of ROS, MDA, and GSSG, breaking the "oxidation-reduction" balance of EC.…”
supporting
confidence: 58%
“…EA.hy 926 cells were exposed to laminar flow with a value of 0 or 3 dyn/cm 2 for 30 min [ 25 ]. LSS significantly reduced the release of NO and PGI 2 and significantly increased the release of ET-1, which was significantly inhibited by 1 mg/L and 10 mg/L DHP, but not by 0.1 mg/L DHP (Figures 4(a) – 4(c) ).…”
Section: Resultsmentioning
confidence: 99%
“…In these cases, control experiments under normoxia/normocapnia could be carried out to evaluate the sole effects of shear stress, but care should be taken in the interpretation, since the possible effects of a double-hit (cyclic hypoxia/hypercapnia plus simultaneous shear stress) challenge effect should not be discarded. In fact, it has recently been found that low shear stress induces endothelial reactive oxygen species (Chao et al, 2018), thereby potentially contributing to the oxidative stress response induced by intermittent hypoxia/hyperoxia.…”
Section: Optimized Control Of Gas Partial Pressure In Cultured Cellsmentioning
confidence: 99%
“…The glycocalyx is composed of many kinds of molecules aside from HA, including heparan sulfate, chondroitin sulfate, and sialic acid, as well as a glycocalyx layer that may not be regulated by the AMPK, NHE1, and HYAL2 axis but is also damaged by LSS. Moreover, we previously reported increased ROS, which degrades HA directly, in HUVECs in response to LSS via the angiotensin II type 1 receptor pathway (34,35). This finding implies that other signaling pathways may participate in LSS-induced glycocalyx impairment.…”
Section: Discussionmentioning
confidence: 80%